2018
DOI: 10.3390/geriatrics3040072
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Concept of ‘Positive Ageing’ in the UK Workplace—A Literature Review

Abstract: The participation rate of older people in the labour market is forecast to increase due to demographic changes afoot. For example, low fertility rates, higher life expectancy, and increases in the retirement age will affect labour availability. The working-age population trends indicate that the age group 55–64 years will expand. This trend is bolstered by policy debate about the sustainability of economic and social support systems for the wider population and necessary strategies to keep older workers in lab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…Older women reported more incidents of discrimination in the form of sexism and ageism, in the workplace across reviews of studies compared to men (Payne and Doyal, 2010;Wilks and Neto, 2013;Edge, Cooper and Coffey, 2017;Diane Keeble-Ramsay, 2018;Edge et al, 2021). This was linked to perceptions of views held by others regarding older women's incompetence and inability to cope with challenges and advancements in the workplace (Payne and Doyal, 2010).…”
Section: Subtheme 4: Sexism Ageism and Isolationmentioning
confidence: 98%
See 2 more Smart Citations
“…Older women reported more incidents of discrimination in the form of sexism and ageism, in the workplace across reviews of studies compared to men (Payne and Doyal, 2010;Wilks and Neto, 2013;Edge, Cooper and Coffey, 2017;Diane Keeble-Ramsay, 2018;Edge et al, 2021). This was linked to perceptions of views held by others regarding older women's incompetence and inability to cope with challenges and advancements in the workplace (Payne and Doyal, 2010).…”
Section: Subtheme 4: Sexism Ageism and Isolationmentioning
confidence: 98%
“…Engels et al (2020) found that on an average, women spent about half as many years in full-time employment than men, while spending more time in part-time or domestic work. The gender employment gap could also be attributed to the fact that women tend to retire earlier than their male counterparts (Edge, Cooper and Coffey, 2017;Diane Keeble-Ramsay, 2018). In their longitudinal study, Weber et al (2019) found that men are more likely to participate in paid employment after retirement compared to women, despite equivalent baseline educational levels.…”
Section: Subtheme 1: Gendered Inequalities and Employmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Beyond accessibility, such a strong emphasis on care and support services also reflects these governments' ideas of ageing, one that focuses on older persons' diminishing abilities, and as a mounting cost to taxpayers (Judd et al, 2020;Moore, 2021). Such a portrayal of older persons is in strong contrast to the increase in academic and community attention on the Third Age and on Positive Ageing, both of which highlight the active contributions older persons can make within and outside their households (Ayalon & Tesch-Römer, 2018;Keeble-Ramsay, 2018;Villar et al, 2021).…”
Section: Age-friendliness Of Australian Policies By Policy Areasmentioning
confidence: 99%
“…Many studies show that, for several decades, the main reasons leading to population ageing include structural population changes, that consequently bring decline in fertility, stagnation in population growth, and new relations in sex, age and population structure [16,17]. Economic and social consequences of the process are broadly analysed [1,18,19]. Priority areas of these changes include the labour market, in which the effects of declining labour resources and their ageing are reflected.…”
Section: Literature Reviewmentioning
confidence: 99%